Perfect : a love story - Soucier, J. C. (Denver, Colo. : Outskirts Press, 2008)
"Father Matthew is a handsome, charismatic man, with a wonderful sense of humor. Kate, after suffering a painful divorce, is thrilled to have met a friend in whom she can confide and feel safe. But as their relationship blossoms, they fall victim to temptation and embark on a journey of forbidden love; a journey that one of the world's most powerful institutions will go to unfathomable lengths to conceal"--p. [4] of cover.
Keywords: Divorced women -- Maine -- Fiction; Pregnant women -- Maine -- Fiction; Catholic Church -- Maine -- Clergy -- Fiction; Man-woman relationships -- Maine -- Fiction; Autobiographical fiction